2018
DOI: 10.2147/ndt.s129559
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on once-monthly long-acting injectable aripiprazole and its potential as maintenance treatment for bipolar I disorder in adult patients

Abstract: The lack of long-term medication adherence is a challenge in the treatment of bipolar disorder, particularly during the maintenance phase when symptoms are less prominent. The rate of nonadherence is ~20%–60% depending on how strict a definition is used. Nonadherence worsens the course of bipolar disorder and can add hundreds of thousands of dollars to the lifetime cost of treating the illness. Long-acting injectable (LAI) medication is an attractive alternative to daily dosing of oral medication, especially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Although AM was more effective than placebo, only about half of the AM-treated participants remained stable for the entire 52-week follow up. The study highlighted the challenge of BD monotherapy: most patients requiring at least 3 drugs, underlining the need for a combination therapy, primarily due to the difficulty of preventing depressive episodes [50,51]. In light of our study results, it seems possible to suggest a maintenance therapy with AM, maintaining PLs at intermediate values.…”
Section: Effectivenessmentioning
confidence: 63%
See 1 more Smart Citation
“…Although AM was more effective than placebo, only about half of the AM-treated participants remained stable for the entire 52-week follow up. The study highlighted the challenge of BD monotherapy: most patients requiring at least 3 drugs, underlining the need for a combination therapy, primarily due to the difficulty of preventing depressive episodes [50,51]. In light of our study results, it seems possible to suggest a maintenance therapy with AM, maintaining PLs at intermediate values.…”
Section: Effectivenessmentioning
confidence: 63%
“…In general, the weight variation was 0.7 %. The literature reports fatigue in 5 % of cases; akathisia is reported in 23 %, insomnia in 10 %, and anxiety in 7 % [50,51].…”
Section: Effectivenessmentioning
confidence: 99%
“…Aripiprazole may be a potential favorable option in the treatment of patients with BD due to its clinical efficacy and the relative lacking of metabolic, endocrine and extrapyramidal effects. There is one large study, some case reports and several reviews that have investigated the efficacy of the once-monthly long-acting aripiprazole formulation (AOM) in the treatment of BD [44][45][46].…”
Section: The Use Of the Sga-lais In The Treatment Of Bdmentioning
confidence: 99%
“…Although the etiology of BD is not yet clear, long-term pharmaceutical treatment is still the most effective methods to ameliorate symptoms and prevent relapses and chronification. However, the high non-adherence rate ranging from 20 to 60% remains as a formidable challenge in the clinical practice for patients with BD ( 3 ). For BD patients with current major depressive episode (MDE), our previous report ( 4 ) has demonstrated that over 60% of treatment interruption occurred within 12 months after treatment initiation, and that over 40% of treatment discontinuation happened in the first 3 months.…”
Section: Introductionmentioning
confidence: 99%